Pemahaman Liberalisme dalam Perspektif Islam dan Kristen Studi terhadap Pandangan Majelis Ulama Indonesia (MUI) dan Persekutuan Injili Indonesia - Harahap, Danil Arif; Hidayat, Muhammad; Harahap, Hotmatua Paralihan (Darul Yasin Al Sys, 2023)
This study discusses the understanding of religious liberalism from an Islamic and Christian perspective. Liberal values are prohibited by the MUI, so Islam is contrary to the basic right to freedom. In rejecting the principle of freedom, the meaning is often misinterpreted as